2006
DOI: 10.1111/j.1462-2920.2006.01187.x
|View full text |Cite
|
Sign up to set email alerts
|

Export of nitrogenous compounds due to incomplete cycling within biological soil crusts of arid lands

Abstract: Second only to water among limiting factors, nitrogen controls the fertility of most arid regions. Where dry and wet depositions are weak, as in the western US deserts, N inputs rely heavily on biological N(2) fixation. Topsoil cyanobacterial communities known as biological soil crusts (BSCs) are major N(2) fixation hot spots in arid lands, but the fate of their fixed N remains controversial. Using a combination of microscale and mesoscale process rate determinations, we found that, in spite of theoretically o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
124
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(137 citation statements)
references
References 44 publications
10
124
2
1
Order By: Relevance
“…Measurements of N 2 O emissions by lichens and bryophytes, too, show considerable variation. Regarding biological soil crusts, several studies analysed denitrification rates to be negligible (Johnson et al, 2007;Strauss et al, 2012), and N 2 O production was calculated to constitute only 3-4 % of the N fixation rate (Barger et al, 2013). Other studies, however, described high denitrification rates that either increased (Brankatschk et al, 2013) or decreased with advancing crust development (Abed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of N 2 O emissions by lichens and bryophytes, too, show considerable variation. Regarding biological soil crusts, several studies analysed denitrification rates to be negligible (Johnson et al, 2007;Strauss et al, 2012), and N 2 O production was calculated to constitute only 3-4 % of the N fixation rate (Barger et al, 2013). Other studies, however, described high denitrification rates that either increased (Brankatschk et al, 2013) or decreased with advancing crust development (Abed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Biocrusts are important to the stability and productivity of dryland ecosystems where plants are typically sparse (Eldridge and Greene, 1994;Belnap et al, 2008;Lindo and Gonzalez, 2010;Zelikova et al, 2012). Previous studies have demonstrated that biocrusts play crucial roles in mediating key processes of N turnover, such as N fixation, nitrification and denitrification (Belnap, 2003;Johnson et al, 2007;Strauss et al, 2012;Abed et al, 2013;DelgadoBaquerizo et al, 2013c;Kidron et al, 2015). Much less, however, is known about the importance of biocrusts on the diversity and abundance of particular microbial communities such as those related to N processes.…”
Section: Introductionmentioning
confidence: 99%
“…However due to increased microbial activities and leaching of N to deeper soil layers (Johnson et al, 2007), nitrogen is still one of the limiting factors in BSCs. Brankatschk et al (2011) demonstrated that deposited N and C are important drivers for the ecosystem development at initial sites; the ability of Cyanobacteria to trap nutrient-rich deposits via their exopolysaccharide sheath even facilitates that effect (Reynolds et al, 2001).…”
Section: S Schulz Et Al: the Role Of Microorganisms In Ecosystem Dementioning
confidence: 99%